The impact of early Holocene Arctic shelf flooding on climate in an atmosphere–ocean–sea–ice model - M. Blaschek; H. Renssen (Climate of the Past, 2013)
Glacial terminations are characterized by a strong rise in sea level related to melting ice sheets. This rise in sea level is not uniform all over the world, because regional effects (uplift and subsidence of coastal zones) are superimposed on global trends. During the early Holocene the Siberian Shelf became flooded before 7.5 ka BP and the coastline reached modern-day high stands at 5 ka BP. This area is currently known as a sea-ice production area and contributes significantly to the sea-ice exported from the Arctic through the Fram Strait. This leads to the following hypothesis: during times of rising sea levels, shelves become flooded, increasing sea-ice production on these shelves, increasing sea-ice volume and export through the Fram Strait and causing the sea-ice extent to advance in the Nordic Seas, yielding cooler and fresher sea surface conditions. We have tested this hypothesis in an atmosphere–ocean–sea–ice coupled model of intermediate complexity (LOVECLIM). Our experiment on early Holocene Siberian Shelf flooding shows that in our model sea-ice production in the Northern Hemisphere increases (15%) and that sea-ice extent in the Northern Hemisphere increases (14%) but sea-ice export decreases (−15%) contrary to our hypothesis. The reason of this unexpected behaviour has its origin in a weakened polar vortex, induced by the land–ocean changes due to the shelf flooding, and a resulting decrease of zonality in the Nordic Seas pressure regime. Hence the winter Greenland high and the Icelandic low strengthen, yielding stronger winds on both sides of the Nordic Seas. Increased winds along the East Greenland Current support local sea-ice production and transport towards the South, resulting in a wider sea-ice cover and a southward shift of convection areas. The overall strength of the Atlantic meridional overturning circulation is reduced by 4% and the heat transport in the Atlantic basin by 7%, resulting in an annual cooling pattern over the Nordic Seas by up to −4 °C. We find that the flooding of the ...